2005
DOI: 10.1016/j.cellbi.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Cellular organisation and differentiation of organelles in pre-meiotic rice anthers

Abstract: Pre-meiotic cellular organisation of rice anthers has a great significance in pollen formation. We have used a combination of confocal laser and transmission electron microscopy (TEM) to characterise and differentiate organelles in pre-meiotic rice anthers. Along with the characteristic organelles in the cytoplasm the epidermal cells of the pre-meiotic rice anther are coated on their outer surface by a conspicuous bi-lamellate cuticle. Chloroplasts of the endothecium contain immature grana, thylakoids and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…When anther walls transitioned from three-to four-layered, at which time the tapetal cells had differentiated, densely stained mitochondria became conspicuous in the cytoplasm of mutant SCs, unlike in the wild-type SCs (Figures 5A and 5B). In wild-type SCs, most mitochondria were composed of indistinct cristae and lessstained matrix ( Figure 5C) (Mamun et al, 2005). On the other hand, the inner wall cells of wild-type and mutant anthers had mitochondria with a very similar appearance, with inflated cristae and densely stained matrix ( Figures 5D and 5F).…”
Section: Loss-of-function Mutation Disrupts the Development Of Archesmentioning
confidence: 86%
“…When anther walls transitioned from three-to four-layered, at which time the tapetal cells had differentiated, densely stained mitochondria became conspicuous in the cytoplasm of mutant SCs, unlike in the wild-type SCs (Figures 5A and 5B). In wild-type SCs, most mitochondria were composed of indistinct cristae and lessstained matrix ( Figure 5C) (Mamun et al, 2005). On the other hand, the inner wall cells of wild-type and mutant anthers had mitochondria with a very similar appearance, with inflated cristae and densely stained matrix ( Figures 5D and 5F).…”
Section: Loss-of-function Mutation Disrupts the Development Of Archesmentioning
confidence: 86%
“…In plant vegetative organs, such as stems and leaves, it is believed that cuticular lipid biosynthesis occurs exclusively within epidermal cells (Sieber et al, 2000;Nawrath, 2002;Panikashvili et al, 2007). Previous reports showed that plastids could not been found in anther epidermal cells (Mamun et al, 2005a(Mamun et al, , 2005b, which implies that lipid de novo synthesis cannot occur within anther epidermal cells. Therefore, it is not surprising that several tapetum-expressed lipid metabolism genes are involved in anther cuticle formation (Li et al, 2010;Shi et al, 2011;Yang et al, 2014).…”
Section: Anther Cuticle and Pollen Exine Share One Common Aliphatic Smentioning
confidence: 91%
“…Glutaraldehyde and paraformaldehyde fixed anthers were embedded in spur's resin, and sections were cut in series with a microtome and stained with uranyl acetate and lead citrate (Mamun et al, 2005). The sections were examined with a Zeiss 902 electron microscope at 80 kV in the Electron Microscope Unit, The University of Sydney, Australia.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Anthers were stained with Rhodamine 123 (Molecular Probes, Eugene, OR, USA) at 10 mg l ÿ1 as previously described (Mamun et al, 2005). A Zeiss LSM 410 confocal attached to a Zeiss Axiovert 200 microscope, or a Zeiss LSM 5 Pascal confocal microscope attached to a Zeiss Axiovert 200M (Carl Zeiss, Germany), was used to collect longitudinal optical sections of the anthers.…”
Section: Mitochondrial Activitymentioning
confidence: 99%
See 1 more Smart Citation